Age, Coastal Proximity, and Salt Consumption: Multifactorial Analysis of Hypertension Risk in A Central Javanese Population - Kumala, Aswa Arsa; Anggitaratri, Zakia Novi; Widyananda, Honesty Trisna; Kurniawati, Yuni Prastyo; Romadhon, Yusuf Alam (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study investigates the relationships between age, salt consumption, coastal proximity, and hypertension risk in populations along the northern coast of Central Java, Indonesia, addressing a significant gap in understanding environmental determinants of hypertension in coastal communities. Methodology: A cross-sectional study analyzed 4,699 patient records from the Integrated Health Post information system in Cepiring Subdistrict, Kendal Regency, Central Java during May-July 2024. Variables examined included age, blood pressure readings, self-reported salt consumption, and coastal proximity (measured as distance from village boundary to coastline). Bivariate analysis using Chi-Square tests and multivariate analysis using binary logistic regression were performed to identify associations and independent risk factors. Results: The study revealed significant associations between all examined factors and hypertension. Advanced age (≥50 years) increased hypertension risk (aOR 1.463; p<0.001). Living within 147 meters of the coastline unexpectedly demonstrated a protective effect (aOR 0.773; p=0.009). Excessive salt consumption showed the strongest association with hypertension (aOR 4.365; p<0.001), presenting a four-fold increased risk compared to moderate or low consumption. Applications/Originality/Value: This study provides novel insights into the paradoxical protective effect of coastal proximity on hypertension risk while confirming the significant impact of age and salt consumption. These findings emphasize the need for targeted interventions addressing dietary management and hypertension prevention, particularly among older populations. The unexpected protective role of coastal proximity warrants further investigation into potential environmental or lifestyle factors unique to coastal communities that might mitigate hypertension risk.